Audição, depressão, cognição e qualidade de vida em pacientes com doença de Parkinson e instabilidade postural - Jordana Carvalhais Barroso (2022)
In patients with Parkinson's Disease (PD), postural instability is an important clinical manifestation. Hearing impairment, cognitive decline and depression are prevalent, associated with greater disability, rapid progression of motor symptoms and increased morbidity and mortality. Patients with PD are vulnerable to deterioration in quality of life. It is important to know the characteristics of this group of patients. Objective: To evaluate hearing, depression, cognitive decline and quality of life in patients with PD and postural instability. Method: This is a descriptive study of patients with PD and postural instability who were evaluated during the period from July 2021 to April 2022 in relation to the frequency and characteristics of hearing loss. Patients with and without hearing loss were compared regarding depression, cognitive decline and quality of life. Results: Thirty patients were evaluated, 18 (60%) of whom were men. Age ranged from 46 to 87 years, median 72 years. The time with the diagnosis of PD ranged from 1 to 15 years, median 9 years. Regarding hearing, 17 (57%) had altered hearing, 10 (59%) of whom were men. All cases of hearing loss were sensorineural, with 14 (82%) being mild loss and 3 (18%) being moderate loss. Use of hearing aids was observed in 1/17 (6%) patient. Regarding the geriatric depression scale, the median was 5 points, with 11 (37%) above 5, characterizing suspicion of depression. The overall median of the values obtained in the Parkinson's Disease Questionnaire39 (PDQ-39) was 47.6, with the highest scores obtained in the bodily discomfort and social support dimensions and, the lowest, in the social stigma dimension. The mini mental state examination was applied to 24/30 (80%) patients, with 18 (75%) presenting values suspected of cognitive alteration. Comparative analysis between individuals with and without hearing loss was carried out, considering comorbidities, medications in use, age group, duration of illness and suspicion of cognitive impairment. Clinical relevance was observed for hearing loss and use of amantadine (p=0.077), diabetes mellitus (p=0.077) and median of 4 years of education (p=0.069). Conclusions: Hearing loss, depression, cognitive decline and compromised quality of life were seen to be common in patients with PD and postural instability.